Application of SARIMA Model for Forecasting Consumption of Electricity in Gezira State, Sudan (2006-2018) - Alamin, Nada Mohammed Ahmed (Journal of natural sciences, life and applied sciences, 2019)
The purpose of the research is to reach the forecast of monthly electricity consumption in Gezira state, Sudan for the period (Jun 2018 - Dec 2020) through the application to the historical data of electric power consumption (Jan 2006-May 2018) obtained from the National Control Center, which has been applied in the research methodology of seasonal Autoregressive Integrated Moving Average due to seasonal behavior in the data, good forecast has been given by SARIMA (2, 1, 7) (0, 1, 1), which has been examined its quality using the Thiel coefficient. The study recommended the use of the model of seasonal Autoregressive Integrated Moving Average in data with Seasonal behavior due to its simple application and accuracy of the results reached.